RITUAL KEAGAMAAN RATIBUL HADDAD DAN SHOLAWAT DIDALAM KEHIDUPAN MASYARAKAT SP 1 DESA MAKMUR SEJAHTERA KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Vica Atmanita; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The tittle of this research is “Religious Ritual Ratibul Haddad and Sholawat in the Society SP 1 Makmur Sejahtera Village Of Gunung Sahilan District Of Kampar Regency”the research was conducted in the village of Makmur Sejahtera of Gunung Sahilan district of Kampar regency. The aim of this research are to find out the function of the Ratibul Haddad and Sholawat for the assembly members and the benefits for the users on certain ocassios, as well as sequence of the event. The method used for this research is descriptive qualitative, a method of research discussions which is presented and analyzed in the form of words (description) with qualitative appoarch. This research is also supported by the use in-depth interviews with the interviewers (informants) who have been previously decided by the researcher. Therefore , the results of the interviewers provide information to support the validity of the research findings. Based of the research findings, this ritual consists of a number of important things which are the function of the Ratibul Haddad and Sholawat for the assembly members and the users on certain ocassions. The Ratibul Haddad and Sholawat ritual is held once a week. The ritual statrs at 8 p.m or after the isya’ prayer until it is done. The Function of the Ratibul Haddad and Sholawat ritual for the assembly members its a mean to generate and strengthen their love for Allah SWT and prophet Muhammad SAW. Furthermore, the function of the Ratibul Haddad and Sholawat ritual for the users on certain occassions is to teach the innocent soul to always remember and love Allah SWT an prophet Muhammad SAW. The event cosinst of apening, hadhiyah, dzikir ratib al-haddad, sholawat, recittion of maulid dibaa’i, preaching, mahallul qiyam, prayer and closing. Keywords : Ritual, Ratib al-Haddad, Sholawat, Majelis